Diatesis Pasif Persona Pertama Tunggal dalam Tindak Tutur Lokusi Menjelaskan oleh Warga Sumberejo, Ambulu, Jember - Ahmad Rizky Wahyudi; Sugeng Adipitoyo (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
As one of grammatical semantics topics, the passive voice of singular first person is used to show the relationship between singular first person (me) and action through the form of passive verbs in a sentence that contain grammatical meaning. The formulation of this research problem is what are the semantic constructions of the passive voice of singular first person in locutionary speech acts explaining based on the strategy in Sumberejo, Ambulu, Jember? This qualitative descriptive research is included in communication ethnographic research. Data was collected through listening and speech methods. Data that has been successfully collected is then presented using categorical, descriptive, and distributional methods. The theories used are Chomsky's generative transformation theory (1965) and Searle's speech act theory (1979). Based on this study, a total of 6 types of passive voice of singular first person in locutionary speech acts explaining in Sumberejo Village, Ambulu District, Jember Regency by dividing the types of passive voice of singular first person based on the form of suffixes and the nature of passive verbs with the type of locutionary speech act explaining based on the strategy. The types of locutionary speech acts explain based on their 5 strategies, then the types are crossed with 5 types of passive voice, singular first person, based on the form of suffixes and the nature of passive verbs